Upaya Preventif Penanggulangan Penyebaran Virus Covid-19 di Kelurahan Beringin Raya - Izharudin; Antoni Sitorus; Romi Gunawan (UNIB Press, 2022)
Beringin Raya has a vulnerability to the spread of the covid-19. This is because Beringin Raya come from various regions, especially boarding house residents, this area is the entrance to Bengkulu City which is directly adjacent to Mukomuko to West Sumatra Province. The purpose of this activity is as an effort to prevent the spread of the Covid-19 in the Beringin Raya Village and to support government programs in overcoming the Covid-19. The activity is in the form of socialization about California papaya cultivation which has benefits for the health (nutrition) of the residents of the Beringin Raya Village. The results that the community in Beringin Raya understands and uses the California Papaya as a medicinal plant in preventing the spread of the covid-19.